Higher malnutrition risk is related to increased intramuscular adipose tissue of the quadriceps in older inpatients: A cross-sectional study. Issue 8 (August 2020) - Akazawa, Naoki; Okawa, Naomi; Hino, Toshikazu; Tsuji, Ryota; Tamura, Kimiyuki; Moriyama, Hideki
Summary: Background & aims: The relationship between malnutrition risk and intramuscular adipose tissue of the quadriceps in older inpatients remains unclear, although a high rate of malnutrition risk has been observed in these patients. Understanding this relationship would be necessary for a management plans for older inpatients. This study aimed to examine the relationship between malnutrition risk and intramuscular adipose tissue of the quadriceps in older inpatients. Methods: Three-hundred and twenty-three older inpatients participated in this cross-sectional study. Malnutrition risk was assessed using the Geriatric Nutritional Risk Index (GNRI). Intramuscular adipose tissue of the quadriceps was assessed based on ultrasound echo intensity. Higher echo-intensity indicates greater amounts of intramuscular adipose tissue. Multiple regression analysis was used to identify the factors that were independently associated with quadriceps echo intensity. GNRI, age, sex (male = 1, female = 2), number of medications, C-reactive protein, updated Charlson comorbidity index, Food Intake Level Scale, the subcutaneous fat thickness of the thigh, motor-Functional Independence Measures, and length of hospital stay were set as the independent variables. Results: GNRI (β = −0.18), age (β = 0.18), sex (β = 0.22), number of medications (β = 0.09), the subcutaneous fat thickness of the thigh (β = −0.29), motor-FIM (β = −0.12), and length of hospital stay (β = 0.11) were significantly and independently associated with the quadriceps echo intensity. Conclusions: The current results revealed that higher malnutrition risk was associated with increased intramuscular adipose tissue of the quadriceps of older inpatients even after adjusting for other characteristics. Nutritional intervention may be necessary for decreasing intramuscular adipose tissue of the quadriceps in older inpatients who have higher malnutrition risk. Highlights: We examined the relation between malnutrition risk and intramuscular adipose tissue. Higher malnutrition risk is related to increased intramuscular adipose tissue. Nutritional intervention may be necessary for decreasing intramuscular adipose tissue.